ALKALINE ULTRAPOTASSIC A-TYPE GRANITES DERIVED FROM ULTRAPOTASSIC SYENITE MAGMAS GENERATED FROM METASOMATIZED MANTLE - Plá Cid J.; Nardi L.V.S. (My University, 2006)
Ultrapotassic Neoproterozoic granites crop out in southern and northeastern Brazil, associated with syenitic suites. The granites occur as small circular bodies and dikes hosted by the syenitic rocks. The southern intrusions reflect post-collisional magmatism, whereas the northeastern granites were emplaced in mobile belts produced during intraplate continental collision. Systematic mineralogical differences of the granites reflect higher K2O/Na2O ratios in the northeastern assemblages. Bulk-rock compositions of the ultrapotassic granites show very high alkalis (mainly K2O) and LIL elements, with significant depletions of Nb, Y, Zr, Hf, Ga, and REE relative to anorogenic granites. These are typical characteristics of ultrapotassic, silica-saturated alkaline rocks from post-collisional settings. Trace- and rare-earth-element patterns suggest derivation by fractional crystallization from syenitic parental magmas. Geochemical and mineralogical characteristics of these granites are completely different from within-plate alkaline granites. Most compositional data are comparable to those of shoshonitic granitoids, suggesting a probable mantle source modified by subducted-slab dehydration. In spite of this, the geochemical composition of the analyzed ultra-potassic granites is also quite different from shoshonitie and calc-alkaline granitoids in collisional settings, defining a silica-saturated ultrapotassic rock series. Copyright © 2006 by V.H. Winston & Son, Inc. All rights reserved.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская